Theory Abstraction

theory Abstraction
imports FuncSet
(*  Title:      HOL/Metis_Examples/Abstraction.thy
    Author:     Lawrence C. Paulson, Cambridge University Computer Laboratory
    Author:     Jasmin Blanchette, TU Muenchen

Example featuring Metis's support for lambda-abstractions.
*)

header {* Example Featuring Metis's Support for Lambda-Abstractions *}

theory Abstraction
imports "~~/src/HOL/Library/FuncSet"
begin

(* For Christoph Benzm├╝ller *)
lemma "x < 1 ∧ ((op =) = (op =)) ==> ((op =) = (op =)) ∧ x < (2::nat)"
by (metis nat_1_add_1 trans_less_add2)

lemma "(op = ) = (λx y. y = x)"
by metis

consts
  monotone :: "['a => 'a, 'a set, ('a *'a)set] => bool"
  pset  :: "'a set => 'a set"
  order :: "'a set => ('a * 'a) set"

lemma "a ∈ {x. P x} ==> P a"
proof -
  assume "a ∈ {x. P x}"
  thus "P a" by (metis mem_Collect_eq)
qed

lemma Collect_triv: "a ∈ {x. P x} ==> P a"
by (metis mem_Collect_eq)

lemma "a ∈ {x. P x --> Q x} ==> a ∈ {x. P x} ==> a ∈ {x. Q x}"
by (metis Collect_imp_eq ComplD UnE)

lemma "(a, b) ∈ Sigma A B ==> a ∈ A ∧ b ∈ B a"
proof -
  assume A1: "(a, b) ∈ Sigma A B"
  hence F1: "b ∈ B a" by (metis mem_Sigma_iff)
  have F2: "a ∈ A" by (metis A1 mem_Sigma_iff)
  have "b ∈ B a" by (metis F1)
  thus "a ∈ A ∧ b ∈ B a" by (metis F2)
qed

lemma Sigma_triv: "(a, b) ∈ Sigma A B ==> a ∈ A & b ∈ B a"
by (metis SigmaD1 SigmaD2)

lemma "(a, b) ∈ (SIGMA x:A. {y. x = f y}) ==> a ∈ A ∧ a = f b"
by (metis (full_types, lifting) CollectD SigmaD1 SigmaD2)

lemma "(a, b) ∈ (SIGMA x:A. {y. x = f y}) ==> a ∈ A ∧ a = f b"
proof -
  assume A1: "(a, b) ∈ (SIGMA x:A. {y. x = f y})"
  hence F1: "a ∈ A" by (metis mem_Sigma_iff)
  have "b ∈ {R. a = f R}" by (metis A1 mem_Sigma_iff)
  hence "a = f b" by (metis (full_types) mem_Collect_eq)
  thus "a ∈ A ∧ a = f b" by (metis F1)
qed

lemma "(cl, f) ∈ CLF ==> CLF = (SIGMA cl: CL.{f. f ∈ pset cl}) ==> f ∈ pset cl"
by (metis Collect_mem_eq SigmaD2)

lemma "(cl, f) ∈ CLF ==> CLF = (SIGMA cl: CL.{f. f ∈ pset cl}) ==> f ∈ pset cl"
proof -
  assume A1: "(cl, f) ∈ CLF"
  assume A2: "CLF = (SIGMA cl:CL. {f. f ∈ pset cl})"
  have "∀v u. (u, v) ∈ CLF --> v ∈ {R. R ∈ pset u}" by (metis A2 mem_Sigma_iff)
  hence "∀v u. (u, v) ∈ CLF --> v ∈ pset u" by (metis mem_Collect_eq)
  thus "f ∈ pset cl" by (metis A1)
qed

lemma
  "(cl, f) ∈ (SIGMA cl: CL. {f. f ∈ pset cl -> pset cl}) ==>
   f ∈ pset cl -> pset cl"
by (metis (no_types) Collect_mem_eq Sigma_triv)

lemma
  "(cl, f) ∈ (SIGMA cl: CL. {f. f ∈ pset cl -> pset cl}) ==>
   f ∈ pset cl -> pset cl"
proof -
  assume A1: "(cl, f) ∈ (SIGMA cl:CL. {f. f ∈ pset cl -> pset cl})"
  have "f ∈ {R. R ∈ pset cl -> pset cl}" using A1 by simp
  thus "f ∈ pset cl -> pset cl" by (metis mem_Collect_eq)
qed

lemma
  "(cl, f) ∈ (SIGMA cl: CL. {f. f ∈ pset cl ∩ cl}) ==>
   f ∈ pset cl ∩ cl"
by (metis (no_types) Collect_conj_eq Int_def Sigma_triv inf_idem)

lemma
  "(cl, f) ∈ (SIGMA cl: CL. {f. f ∈ pset cl ∩ cl}) ==>
   f ∈ pset cl ∩ cl"
proof -
  assume A1: "(cl, f) ∈ (SIGMA cl:CL. {f. f ∈ pset cl ∩ cl})"
  have "f ∈ {R. R ∈ pset cl ∩ cl}" using A1 by simp
  hence "f ∈ Id_on cl `` pset cl" by (metis Int_commute Image_Id_on mem_Collect_eq)
  hence "f ∈ cl ∩ pset cl" by (metis Image_Id_on)
  thus "f ∈ pset cl ∩ cl" by (metis Int_commute)
qed

lemma
  "(cl, f) ∈ (SIGMA cl: CL. {f. f ∈ pset cl -> pset cl & monotone f (pset cl) (order cl)}) ==>
   (f ∈ pset cl -> pset cl)  &  (monotone f (pset cl) (order cl))"
by auto

lemma
  "(cl, f) ∈ CLF ==>
   CLF ⊆ (SIGMA cl: CL. {f. f ∈ pset cl ∩ cl}) ==>
   f ∈ pset cl ∩ cl"
by (metis (lifting) CollectD Sigma_triv subsetD)

lemma
  "(cl, f) ∈ CLF ==>
   CLF = (SIGMA cl: CL. {f. f ∈ pset cl ∩ cl}) ==>
   f ∈ pset cl ∩ cl"
by (metis (lifting) CollectD Sigma_triv)

lemma
  "(cl, f) ∈ CLF ==>
   CLF ⊆ (SIGMA cl': CL. {f. f ∈ pset cl' -> pset cl'}) ==>
   f ∈ pset cl -> pset cl"
by (metis (lifting) CollectD Sigma_triv subsetD)

lemma
  "(cl, f) ∈ CLF ==>
   CLF = (SIGMA cl: CL. {f. f ∈ pset cl -> pset cl}) ==>
   f ∈ pset cl -> pset cl"
by (metis (lifting) CollectD Sigma_triv)

lemma
  "(cl, f) ∈ CLF ==>
   CLF = (SIGMA cl: CL. {f. f ∈ pset cl -> pset cl & monotone f (pset cl) (order cl)}) ==>
   (f ∈ pset cl -> pset cl) & (monotone f (pset cl) (order cl))"
by auto

lemma "map (λx. (f x, g x)) xs = zip (map f xs) (map g xs)"
apply (induct xs)
 apply (metis list.map(1) zip_Nil)
by auto

lemma
  "map (λw. (w -> w, w × w)) xs =
   zip (map (λw. w -> w) xs) (map (λw. w × w) xs)"
apply (induct xs)
 apply (metis list.map(1) zip_Nil)
by auto

lemma "(λx. Suc (f x)) ` {x. even x} ⊆ A ==> ∀x. even x --> Suc (f x) ∈ A"
by (metis mem_Collect_eq image_eqI subsetD)

lemma
  "(λx. f (f x)) ` ((λx. Suc(f x)) ` {x. even x}) ⊆ A ==>
   (∀x. even x --> f (f (Suc(f x))) ∈ A)"
by (metis mem_Collect_eq imageI set_rev_mp)

lemma "f ∈ (λu v. b × u × v) ` A ==> ∀u v. P (b × u × v) ==> P(f y)"
by (metis (lifting) imageE)

lemma image_TimesA: "(λ(x, y). (f x, g y)) ` (A × B) = (f ` A) × (g ` B)"
by (metis map_prod_def map_prod_surj_on)

lemma image_TimesB:
    "(λ(x, y, z). (f x, g y, h z)) ` (A × B × C) = (f ` A) × (g ` B) × (h ` C)"
by force

lemma image_TimesC:
  "(λ(x, y). (x -> x, y × y)) ` (A × B) =
   ((λx. x -> x) ` A) × ((λy. y × y) ` B)"
by (metis image_TimesA)

end